Moisture sorption isotherms and heat of sorption of mango (Magnifera Indica L. cv. Nam Dok Mai) - S. Janjai (2018)
The equilibrium moisture contents of the Thai mango variety 'Nam Dok Mai' were determined using the dynamic method at temperatures of 30-50°C and water activity from 0.11-0.97. The sorption isotherm curves obtained displayed an inverse relationship with temperature at constant relative humidity. Six selected isotherm models were tested against the experimental isotherm data and the models were compared using standard error of estimate, mean relative error, coefficient of determination and residual plots. Among the models tested, GAB model was the best fitting for the temperatures of 30, 40, and 50°C. The fitting of the Day and Nelson model, and the modified Smith model was very close and it is next to the GAB model. These models can be considered and used with good predictive accuracy to determine the equilibrium moisture contents of the Thai mango variety 'Nam Dok Mai'. The isosteric heats of sorption were also determined from the equilibrium data using the Clausius-Clapeyron equation and were found to be exponential functions of moisture content. This equation is suggested for use in the computation of heat of sorption of mango slices. © 2007 AAAE.